Case Based Reasoning And Naive Bayes Implementation In Laptop Purchasing Recommender System - Dharmawangsa, I Gusti Ngurah Agung; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Purchasing a new laptop will be difficult if we do not know what the ideal laptop specification for our needs. Especially with a wide selection of laptops. From this problem, system that can give a recommendation to choose the right laptop based on purchaser’s specification choice is needed. This research using two method, Case Based Reasoning and Naive Bayes . The concept of Case Based Reasoning is  the process of solving new problems based on the solutions of similar past problems ,  While Naive Bayes assumes that the presence of a particular feature in a class is unrelated to the presence of any other feature. Naive bayes will be implemented in retrive process of case based reasoning. The recommender system utilizing 7 feature, Kecepatan Processor, Kapasitas Ram, Tipe Grafis, Ukuran Layar, Ukuran Harddisk, Kecepatan Layar, and Harga. The percentage of respondents who said the system was successful in providing the right recommendations was 70 percent of the total respondents.